2016
DOI: 10.3389/fmicb.2016.02038
|View full text |Cite
|
Sign up to set email alerts
|

Fluconazole and Echinocandin Resistance of Candida glabrata Correlates Better with Antifungal Drug Exposure Rather than with MSH2 Mutator Genotype in a French Cohort of Patients Harboring Low Rates of Resistance

Abstract: Candida glabrata is a major pathogenic yeast in humans that is known to rapidly acquire resistance to triazole and echinocandin antifungal drugs. A mutator genotype (MSH2 polymorphism) inducing a mismatch repair defect has been recently proposed to be responsible for resistance acquisition in C. glabrata clinical isolates. Our objectives were to evaluate the prevalence of antifungal resistance in a large cohort of patients in Saint-Louis hospital, Paris, France, some of whom were pre-exposed to antifungal drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
68
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 41 publications
10
68
1
Order By: Relevance
“…We did not find any correlation between the presence of MSH2 gene mutations and the acquisition of antifungal resistance either in vitro or in clinical settings. This is in line with previous studies in which this lack of correlation was also highlighted (16,17,19).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We did not find any correlation between the presence of MSH2 gene mutations and the acquisition of antifungal resistance either in vitro or in clinical settings. This is in line with previous studies in which this lack of correlation was also highlighted (16,17,19).…”
Section: Discussionsupporting
confidence: 93%
“…Here, the rate of isolates harboring mutations in the MSH2 gene (44.4%) is similar to that reported in some other studies (15,17) but lower than the 77.2% reported by Hou et al (19). Certain mutations, such as V239L and P208S/N890I, have been associated with resistance (15,17), whereas others that are less common, E7K, E456D, or E459K, have not (15)(16)(17).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the context of adhesins, which are enriched in repetitive elements, MSH2 defects may perhaps contribute to increase the diversity of this gene family over generations. It has been observed that 44-50% of investigated isolates (n=625) were carrying MSH2 defects and thus indicate that MSH2 defect may confer some selective advantage in C. glabrata (Healey, Zhao, et al 2016; Healey, Jimenez-Ortigosa, et al 2016; Dellière et al 2016). In agreement with our hypothesis, it is interesting to mention that CBS138 and CCTCC M202019 do not exhibit MSH2 defects and contains a limited repertoire of adhesins as compared to DSY562/DSY565.…”
Section: Discussionmentioning
confidence: 99%